Russia’s Views on and Initial Responses to the 2021 Strategic Retake of Afghanistan by the Taliban - Muraviev, Alexey (SAGE Journals, 2022)
The Taliban’s return to power in Afghanistan in mid-2021 has not taken the Russian authorities by surprise. For over 20 years, Moscow was observing the strategic rise of the fundamentalist militant movement with concern, which was largely triggered by domestic security considerations as well as potential challenges to security and stability across the former Soviet Central Asia. However, since the re-establishment of the Taliban’s rule in Kabul, Moscow’s approach underwent a gradual change, from being negative and alarmist to a more cautiously pragmatic one. This article will review the evolution of Russia’s perceptions of the Taliban, highlight Moscow’s principal concerns, identify the initial set of response measures following the country’s takeover in 2021 and entertain several scenarios of the Kremlin’s future approaches vis-a-vis the new rulers in Kabul.